Preparation of a highly specific single chain variable fragment antibody targeting miroestrol and its application in quality control of Pueraria candollei by enzyme‐linked immunosorbent assay. Issue 6 (25th April 2019) - Pongkitwitoon, Benyakan; Boonsnongcheep, Panitch; Kitisripanya, Tharita; Yusakul, Gorawit; Sakamoto, Seiichi; Tanaka, Hiroyuki; Morimoto, Satoshi; Putalun, Waraporn
Abstract: Introduction: Miroestrol is the potent phytoestrogen isolated from White Kwao Krua ( Pueraria candollei var. mirifica (Airy Shaw & Suvat.) Niyomdham, a Thai traditional medicinal plant. Nowadays, various health supplementary products featuring White Kwao Krua are available worldwide. A sensitive and rapid analytical method for quantification of miroestrol is necessary for quality control of these products. Objectives: To prepare a single‐chain variable fragment (scFv) antibody specific to miroestrol and develop a scFv‐based enzyme‐linked immunosorbent assay (ELISA) for quantitative analysis of miroestrol in plant materials and health supplementary products. Methods: A gene encoding anti‐miroestrol scFv antibody was constructed and expressed in Escherichia coli SHuffle T7 strain. Anti‐miroestrol scFv antibody was characterised and applied to ELISA. The developed scFv‐based ELISA method was validated for its sensitivity, specificity, accuracy and precision. Results: Anti‐miroestrol scFv antibody was highly specific to miroestrol. The scFv‐based ELISA was applied to determine miroestrol in the range 0.06–7.81 μg/mL, with the limit of quantification of 0.06 μg/mL miroestrol. The accuracy of the assay was validated by its 95.08–103.99% recovery from the spiked miroestrol recovery experiment and in good correlation with the results from the monoclonal antibody‐based ELISA. The relative standard deviation of the intra‐ and inter‐assay were less than 6.0%. Conclusion: The developed scFv‐based ELISA was sensitive, specific, accurate, and precise for determination of miroestrol and useful for quality control of P. candollei plant raw materials and supplementary products. Abstract : A gene encoding single chain variable fragment antibody (scFv) targeting miroestrol, a potent phytoestrogen from Pueraria candollei, was constructed and expressed using E. coli Shuffle T7 strain. Anti‐miroestrol scFv‐based ELISA was developed with a quantification range of miroestrol of 0.06 ‐ 7.81 microgram/mL. The developed assay was validated for quantitative analysis of miroestrol in plant samples and related products.